Perinatal ischemic stroke as a misunderstood cause of cerebral palsy: Literature review, future perspectives and forensic problems - Gaetano Buonocore; Giuseppe De Bernardo; Marianna De Falco; Francesco Menale; Maurizio Giordano; Andrea Di Lieto (Elsevier, 2022)
Neonatal encephalopathy is a relatively common clinical condition which results in serious consequences including death, cerebral palsy, epilepsy and other cognitive, developmental and behavioral problems. In 1966 some researchers found that many cases of congenital lesions of the cerebral cortex, basal ganglia and other suprasegmental structures showed symptoms and signs many months after birth. Currently, many children with non-perinatal neurological history present later in infancy with neurological abnormalities, usually hemiparesis, that is attributable to remote focal infarction on neuroimaging. Although intrapartum asphyxia accounts for less the 10% of cases of cerebral palsy, it represents a leading claim in obstetric malpractice litigation. So, in confirmed cases of neonatal encephalopathy, the likelihood that it was determined by an acute intrapartum or peripartum event should be determined. ACOG Task Force on Neonatal Encephalopathy recommended a multidimensional assessment process for neonatal encephalopathy and defined diagnostic criteria. On the other hand, there is growing evidence that ischemic perinatal stroke is the leading known cause of hemiplegic cerebral palsy, with an incidence of 1:3000 live births or more. Object of this paper is to report 3 cases series affected by ischemic perinatal stroke and review the classification and diagnostic criteria of both neonatal and ischemic perinatal stroke, with the aim of speculate that IPS due to perinatal hypoxia could lead to cerebral palsy also without evidences of neonatal encephalopathy close to birth and increase litigation for obstetric malpractice.